PENGARUH KOMPETENSI, MOTIVASI DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT. BANK PEMBANGUNAN DAERAH BALI CABANG RENON DENPASAR - I Gusti Bagus Wira Kurnia Saputra; Ni Made Dwi Puspitawati; Ni Luh Gede Putu Purnawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
High employee performance is expected by every company. The more employees who have high performance, the overall company productivity will increase. This study aims to determine the effect of competence, motivation and physical work environment on employee performance. This research was conducted at PT. Regional Development Bank Bali Renon Denpasar Branch using a sample and a population of 53 people as research respondents. The sampling method used is the saturated sampling method or the census method. Data was collected through observation, interviews, documentation and questionnaires. The data analysis technique used in this research is multiple linear regression analysis which is processed using the SPSS version 21.0 for windows program. Based on the results of the analysis, this study shows that competence has a positive and significant effect on employee performance, which means the more competence increases, the performance at PT. Bali Regional Development Bank Renon Denpasar Branch increased. Motivation has a positive and significant effect on employee performance, which means the more motivation increases, the performance at PT. Bali Regional Development Bank Renon Denpasar Branch increased. The physical work environment has a positive and significant effect on performance, which means the better the work environment provided by the company, the performance at PT. Bali Regional Development Bank Renon Denpasar Branch increased.